Dinamika konflik interpersonal antara mertua dan menantu yang tinggal serumah - Sirojuttholibin, Muhamad (Maliki Interdisciplinary Journal, 2024)
In the early days of marriage, many young couples choose to live with their parents, especially the husband. In this case, the wife has to live with her husband. This can cause problems and conflicts in the household. One of the things that often happens in families is conflict between in-laws and daughters-in-law who live in the same house. Different cultural backgrounds, different values and norms, and different roles and responsibilities can cause this conflict. The forms caused by this conflict vary, ranging from arguing to not saying hello. Thus causing domestic relationships to heat up. Resolution in conflict is needed in order to bring back household harmony.